The autisms - Coleman, Mary, 1928-; Gillberg, Christopher, 1950-; Gillberg, Christopher, 1950- (New York : Oxford University Press, 2012)
This title aids the clinician to diagnose autism and autism/epilepsy, and to learn what is known about the epidemiology, neuroanatomy, biochemistry, neuropsychology and genetics.
Previous ed.: published in print as Biology of the autistic syndromes by Christopher Gillberg, Mary Coleman. 2000.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Autism in children; Autism in children -- Etiology; Child development deviations -- Physiological aspects